Nitrogen fertilization effects on yield and quality of durum wheat in the Ebro Valley (Spain) - Abad A.; Lloveras J.; Michelena A.; Ferrán J. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
The study evaluated the effects of nitrogen fertilization (0, 50, 100, 150 and 200 kg N ha-1) on durum wheat (Triticum turgidum L. var durum ) yield and quality (crude protein, carotenoids and vitreousness) during two growing seasons 1994-95 and 1995-96 in two locations of the Ebro Valley. Durum wheat yield and quality increased with increasing N fertilization. In Torregrossa (TOR) the average grain yield increased from 2.728 to 3.476 kg ha-1, when N fertilization rates increased from 0 to 200 kg N ha-1, whereas in Bell-lloc (BELL) with an average yield of 4.257 kg per ha, N fertilization did not increase grain yield. Crude protein (CP) and carotenoids increased with N fertilization rates in both locations, whereas vitreousness only increased in TOR. CP contents increased from 12.5 to 15.2 per cent in TOR and from 15.0 and 15.8 per cent in BELL when N rates increased from 0 to 200 kg ha-1. Carotenoids increased from 9.25 to 10.94 ppm in TR and from 10.11 to 10.55 ppm in Bell-lloc.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)